2019
DOI: 10.4012/dmj.2018-253
|View full text |Cite
|
Sign up to set email alerts
|

Bond strengths between gingiva-colored layering resin composite and zirconia frameworks coated with feldspathic porcelain

Abstract: This study evaluated shear bond strengths of two gingiva-colored layering resin composites to zirconia frameworks coated with feldspathic porcelain. Airborne-particle abraded porcelain-coated zirconia disks were treated with one of the following primers: Clearfil Photo Bond, Clearfil Photo Bond with Clearfil Porcelain Bond Activator (CPB+Activator), Estenia Opaque Primer, Porcelain Liner M Liquid B (PLB), or no primer. A light-polymerizing (CER) or a photo/heat-polymerizing gingiva-colored indirect resin compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 28 publications
(31 reference statements)
0
9
0
Order By: Relevance
“…In the presence of alveolar resorption, resection, and asymmetry, in cases where surgical or regenerative procedures are performed, soft and hard tissue augmentation is not always possible, and gingiva‐colored materials are used to layer the framework materials 3 . In addition, patients sometimes reject surgical interventions due to pain and associated discomfort, prolonged healing time, and cost of surgery 4 . Use of autopolymerizing acrylic resins, silicone materials, gingiva‐colored porcelains, and composite resins is an alternative to reconstructing defective tissues 1–4 .…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…In the presence of alveolar resorption, resection, and asymmetry, in cases where surgical or regenerative procedures are performed, soft and hard tissue augmentation is not always possible, and gingiva‐colored materials are used to layer the framework materials 3 . In addition, patients sometimes reject surgical interventions due to pain and associated discomfort, prolonged healing time, and cost of surgery 4 . Use of autopolymerizing acrylic resins, silicone materials, gingiva‐colored porcelains, and composite resins is an alternative to reconstructing defective tissues 1–4 .…”
mentioning
confidence: 99%
“…As the veneering procedure needs many steps, it is time‐consuming and requires technical precision 5 . Recent studies have reported that the gingiva‐colored composite is a promising alternative to porcelain 2–4 . It offers a faster, easier, and comparatively less expensive veneering option, which does not shrink during firing.…”
mentioning
confidence: 99%
See 3 more Smart Citations